Replikasi Fungsi Wali Amanat/Agen Pemantau Pada Layanan Urun Dana Peer To Peer Landing Dan Securities Crowdfunding Efek Bersifat Utang/Sukuk - Firdinal, Ziffany (UNIB Press, 2024)
This paper tries to compare the Public Offering in Capital Market activities with Crowdfunding activities (Peer to Peer Lending and Securities Crowdfunding on Bond/Sukuk) which are basically identical because the wider community can access offers from borrowers and make funding through platforms that can be accessed by the public. According to the results of research by the Financial Services Authority of Indonesia in 2017, there are inherent risks in the Crowdfunding base on Peer-to-Peer Lending services, namely the risk of default and lack of information for investors, therefore it is proposed to replicate the Bond Trustee Institution which plays a role in protecting the interests Bond/Sukuk offered in a Public Offering in Crowdfunding activities of Peer-to-Peer Lending and Securities Crowdfunding on Bond/Sukuk. Keyword: Crowdfunding, trustee, Securities